PENGARUH JUMLAH DAN KRITERIA BUAH MUDA YANG DIPERTAHANKAN TERHADAP HASIL BUAH MANGGA ( EFFECT OF NUMBER AND CRITERIA OF MAINTAINED YOUNG FRUITS ON YIELD OF MANGO) - , Sakhidin (Pembangunan Pedesaan, 2010)
The aim of this research was to get optimum number of maintained young fruit per panicle and good criteria of fruit that must be maintained so it will get a high yield of mango. The factors under investigation were number of young fruit to be maintained per panicle: 2, 4, and 6; the criteria of young fruit to be maintained: the biggest fruit, fruit attached at the beginning of panicle, and fruit attached at panicle at the same distance. The result of research showed that 6 fruits that maintained per panicle gave the highest weight per tree of mango (33,45 kg), but the lowest weight per fruit (466,98 kg). Maintaining the 2 biggest fruits of mango gave the highest weight per fruit (510,53 g).